Relationship between neutrophil-lymphocyte ratio and severity of lower extremity peripheral artery disease. (1st February 2017) - Teperman, Jacob; Carruthers, David; Guo, Yu; Barnett, Mallory P.; Harris, Adam A.; Sedlis, Steven P.; Pillinger, Michael; Babaev, Anvar; Staniloae, Cezar; Attubato, Michael; Shah, Binita
Abstract: Background: The aim of this study was to determine the association between neutrophil-lymphocyte ratio (NLR) and severity of lower extremity peripheral artery disease (PAD). Methods: A retrospective chart review identified 928 patients referred for peripheral angiography. NLR was assessed from routine pre-procedural hemograms with automated differentials and available in 733 patients. Outcomes of interest were extent of disease on peripheral angiography and target vessel revascularization. Median follow-up was 10.4 months. Odds ratio (OR) [95% confidence intervals] was assessed using a logistic regression model. Results: There was a significant association between elevated NLR and presence of severe multi-level PAD versus isolated suprapopliteal or isolated infrapopliteal disease (OR 1.11 [1.03–1.19], p = 0.007). This association remained significant even after adjustment for age (OR 1.09 [1.01–1.17], p = 0.02); age, sex, race, and body mass index (OR 1.08 [1.00–1.16], p = 0.046); and age, sex, race, body mass index, hypertension, diabetes mellitus, coronary artery disease, and creatinine (OR 1.07 [1.00–1.15], p = 0.049). After additional adjustment for clinical presentation, there was a trend towards association between NLR and severe multi-level PAD (OR 1.07 [1.00–1.15], p = 0.056), likely limited by sample size. In patients who underwent endovascular intervention (n = 523), there was no significant difference in rate of target vessel revascularization across tertiles of NLR (1st tertile 14.8%, 2nd tertile 14.1%, 3rd tertile 20.1%; p = 0.32). Conclusion: In a contemporary cohort of patients undergoing peripheral angiography with possible endovascular intervention, elevated NLR was independently associated with severe multi-level PAD. Larger studies evaluating the association between this inexpensive biomarker and clinical outcomes are warranted.